Investor Protection and Asset Prices - Basak, Suleyman; Chabakauri, Georgy; Yavuz, M Deniz (Review of Financial Studies, 2019)
Abstract Empirical evidence suggests that investor protection significantly affects ownership concentration and asset prices. We develop a dynamic asset pricing model to address the empirical regularities and uncover some of the underlying mechanisms at play. Our model features a controlling shareholder that endogenously accumulates control over a firm, and diverts a fraction of its output. Better investor protection decreases stock holdings of controlling shareholders, increases stock mean returns, and increases stock return volatilities when ownership concentration is sufficiently high, consistent with the related empirical evidence. The model also predicts that better protection increases interest rates and decreases the controlling shareholder’s leverage. Received August 14, 2017; editorial decision January 15, 2019 by Editor Stijn Van Nieuwerburgh. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.